2020
DOI: 10.1371/journal.pone.0240566
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic membranous nephropathy in older patients: Clinical features and outcomes

Abstract: Background Various factors can affect renal and patient outcome in idiopathic membranous nephropathy (iMN). We aimed to identify predictors of renal and patient survival in patients with iMN, with a special focus on outcomes among older patients. Methods We retrieved data on 1,776 patients (mean age 53.0 ± 14.7 years; 1,075 [60.5%] males) diagnosed with iMN from the Korean GlomeruloNEphritis sTudy (KoGNET), a database compiled from 18 centers in Korea. Results The cohort included 428 (24.1%) patients over 65 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Conventional Western medicine treatment of IMN has a long cycle and large drug toxicity and side effects, and the patient's compliance with treatment is low. In addition, the individual differences of patients are large, resulting in poor efficacy [ 1 ]. Therefore, it is necessary to find new safe and effective treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional Western medicine treatment of IMN has a long cycle and large drug toxicity and side effects, and the patient's compliance with treatment is low. In addition, the individual differences of patients are large, resulting in poor efficacy [ 1 ]. Therefore, it is necessary to find new safe and effective treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence may be underestimated because only a small proportion of patients with MN progress to end-stage kidney disease (ESKD). Adults over the age of 50 are more commonly affected [19][20][21]. MN is defined by its characteristic histopathological features, which include thickened glomerular basement membrane and subepithelial spikes on the outer surface of the capillary wall.…”
Section: Introductionmentioning
confidence: 99%
“…They are usually recognized as the indices to evaluate anemia. Compared with younger patients, idiopathic membranous nephropathy patients over 65 years old were found to have lower Hb level than patients less than 65 years old in Choi JY’s study 34 . However, the results in Yaeni Kim’s study showed there was no difference of Hb levels between elderly patients and young patients 35 .…”
Section: Discussionmentioning
confidence: 78%